Rival reputations : coercion and credibility in US-North Korea relations - Jackson, Van, 1982- (Cambridge University Press, 2016)
"The Puzzle: In March 2013, the North Korean Central News Agency (KCNA) warned of a 'pre-emptive nuclear attack' if the United States convinced the UN Security Council to impose new economic sanctions on North Korea. Despite this warning the Security Council did impose new sanctions at U.S. urging, on March 7. No nuclear attack came. Two weeks later, KCNA released a video of North Korea's leader, Kim Jong Un, discussing a plan for launching nuclear-armed missiles against U.S. bases in the Pacific and the continental United States. The imagery of Kim Jong Un pointing to maps of the United States with arrows outlining missile trajectories was a vivid accompaniment to recent warnings from North Korea's media organs that the North Korean People's Army (KPA) will 'destroy not only the military installments ... of South Korea but the ... military bases of the U.S. imperialist aggression forces in the operational theatre of the Pacific.' No attack followed"--Provided by publisher